KRITERIA DAN KARAKTERISTIK AKUNTAN DALAM PERSPEKTIF ISLAM - Harjoni; Syamsul Rijal; Angga Syahputra (J-ISCAN: Journal of Islamic Accounting Research, 2021)
The accountants are a profession that has existed since the era of the Prophet Muhammad. Related to taking notes, and counting activities, Rasulullah SAW implemented and educated his companions to become officers (katibul amwaal), accountants (hafazhatul amwaal) because apart from being a prophet, Rasulullah SAW was a good businessman. This article aims to explore the Shirah Nabawiyah (library study) to give us an idea of who accountants were in the era of the Prophet and what their characteristics were. Based on the literature review, there are several companions who were positioned by the Prophet Muhammad specifically for financial management (the state) and even the Prophet divided them into seven functions, six accounting functions and one function for auditing (audit).